An Overview of modeling of nano-composite materials and structures - Mohammed Ridha H Alhakeem (Brilliance: Research of Artificial Intelligence, 2022)
The research conducted by many scientists and engineers on nanocomposite materials and continuous systems made from such materials will be reviewed historically in this article by the writers. Nano composites are a form of well-known composite material that has been improved by adding nanoscale fibers and/or particles for reinforcement. These materials may be more appropriate for industrial applications that require material qualities that are noticeably improved. In other words, because of the improved properties of materials at the nanoscale, the material properties of nanocomposites are superior to those of macroscale composites. Designers are using these materials more frequently than traditional composite materials as constituent parts in aerospace, mechanical, and automotive applications. In order to forecast how buildings made of these materials will behave under actual operating conditions, it is crucial to be aware of the research that has been done in this field. The mechanical analyses carried out on various nanocomposite structures, such as those reinforced with carbon nanotubes (CNTR), graphene (GR), graphene platelets (GPLR), graphene oxide (GOR), and multi-scale hybrid (MSH) nano-composite ones, will be reviewed in the sections that follow, along with the most significant aspects of the suggested scientific activities.